From Collaboration to Innovation: Strengthening Teacher Reflection and Professionalism Through Lesson Study for Learning Community - Sagita, Laela; Utami, Niken Wahyu; Darsono, Darsono; Fauziah, Muhardila (Jurnal Karya Abdi Masyarakat, 2025)
This community service program aimed to support the activities of Kombel Muga Berkemajuan at Muhammadiyah 3 Junior High School Yogyakarta and to strengthen teacher professionalism, particularly in reflective capacity and classroom innovation. The program was carried out using the Lesson Study for Learning Community (LSLC) approach, emphasizing collaborative planning, classroom implementation, and shared reflection. A qualitative descriptive method was applied, with data obtained through classroom observations, reflective discussions, and documentation analysis. The implementation consisted of three main stages: identifying partner readiness, preparing mentoring activities, and conducting LSLC cycles (plan–do–see). The findings show that the LSLC activities encouraged teachers to engage in more evidence-based reflection when analyzing teaching and learning processes. Teachers also began experimenting with contextual, problem-based, and text-based lesson designs that contributed to richer classroom discussions across Mathematics, Social Studies, and Indonesian Language. Kombel Muga Berkemajuan gradually developed into a more functional professional learning community, with collaboration becoming part of teachers’ routine practice. Challenges observed included limited time, instructional resources, and difficulties in applying differentiated instruction. These challenges indicate the need for continued mentoring and capacity building. Overall, the program highlights the potential of LSLC to support teacher professionalism and strengthen collaborative culture in Muhammadiyah schools.